Implementation of IoT Edge Computing for Control and Monitoring System of Hydroponic Plant Water Quality Using Raspberry Pi - Cahya Lukito; Rony Baskoro Lukito; Endang Ernawati (International Journal of Computer Science and Humanitarian AI, 2024)
Hydroponics involves cultivating plants using a water-based medium mixed with mineral nutrients, continuously supplied to the roots 24/7. Factors such as water reserve height, temperature, nutrient content, and pH are crucial considerations in hydroponic farming. Connectivity issues to the internet-based cloud system can disrupt the monitoring and control system. To ensure the effective operation of the hydroponic plant control and monitoring system, IoT edge computing within the Local Area Network is necessary as an extension of the cloud system. Periodically, the system will transmit calculation results from water quality sensors to the cloud-based system through IoT edge computing, enabling decision-making within the Local Area Network and subsequent transmission to Internet of Things devices within the hydroponic system for optimal plant growth.